SIZE EFFECT AND STOCK BEHAVIOR DURING THE EXPANSION AND CONTRACTION PHASES OF ECONOMIC CYCLE: An Empirical Evidence from Indonesian Stock Market - Asri, Marwan (Gadjah Mada International Journal of Business, 2002)
Banz (1981) and Reiganum (1981) claim that, in terms of returncreation, small firms tend to perform better than large firms. They implicitly claim that the phenomena (which is known as size effect) is stable and exists over the period of examination. This study intends to investigate the existence of size effect in Indonesian market and more specifically, to test whether stages of economic cycle (expansion and contraction stages) determine the existence of the effect. The results of the study show that size effect does exist in the market for the whole period of observation (1991-2001). However, when the period is divided into two parts according to the stage of economic cycle, theÂ  statistical analysis results are not supportive to the conclusion about the size effect.